Investigation of SARS-CoV-2 outbreaks in six care homes in London, April 2020 - Ladhani, Shamez N; Chow, J.Yimmy; Janarthanan, Roshni; Fok, Jonathan; Crawley-Boevey, Emma; Vusirikala, Amoolya; Fernandez, Elena; Perez, Marina Sanchez; Tang, Suzanne; Dun-Campbell, Kate; Evans, Edward Wynne; Bell, Anita; et al. (EClinicalMedicine, 2020)
Background: Care homes are experiencing large outbreaks of COVID-19 associated with high case-fatality rates. We conducted detailed investigations in six London care homes reporting suspected COVID-19 outbreaks during April 2020. Methods: Residents and staff had nasal swabs for SARS CoV-2 testing using RT-PCR and were followed-up for 14 days. They were categorized as symptomatic, post-symptomatic or pre-symptomatic if they had symptoms at the time of testing, in the two weeks before or two weeks after testing, respectively, or asymptomatic throughout. Virus isolation and whole genome sequencing (WGS) was also performed. Findings: Across the six care homes, 105/264 (39.8%) residents were SARS CoV-2 positive, including 28 (26.7%) symptomatic, 10 (9.5%) post-symptomatic, 21 (20.0%) pre-symptomatic and 46 (43.8%) who remained asymptomatic. Case-fatality at 14-day follow-up was highest among symptomatic SARS-CoV-2 positive residents (10/28, 35.7%) compared to asymptomatic (2/46, 4.3%), post-symptomatic (2/10, 20.0%) or pre-symptomatic (3/21,14.3%) residents. Among staff, 53/254 (20.9%) were SARS-CoV-2 positive and 26/53 (49.1%) remained asymptomatic. RT-PCR cycle-thresholds and live-virus recovery were similar between symptomatic/asymptomatic residents/staff. Higher RT-PCR cycle threshold values (lower virus load) samples were associated with exponentially decreasing ability to recover infectious virus (P<0.001). WGS identified multiple (up to 9) separate introductions of different SARS-CoV-2 strains into individual care homes. Interpretation: A high prevalence of SARS-CoV-2 positivity was found in care homes residents and staff, half of whom were asymptomatic and potential reservoirs for on-going transmission. A third of symptomatic SARS-CoV-2 residents died within 14 days. Symptom-based screening alone is not sufficient for outbreak control. Funding: None